Pengaruh Online Store Atmosphere dan Promosi Terhadap Pembelian Impulsif Di Mediasi Oleh Emosi Positif - Agistia Zalfa Nasihah; Nur Laili Fikriah (Universitas YARSI, 2023)
The purpose of this study is to analyze the impact of online store atmosphere and promotions on impulse buying are mediated by positive emotions in shopee users. This study employed the path analysis approach with the SmartPLS 3.0 software. The sample of this study is shopee users that totaling 115 respondens decide through purposive sampling. The result of this study is shows that online store atmosphere has no affect to impulse buying, while promotion and positif emotion has affect to impulse buying. Besides that online store atmosphere and promotions have an indirect affect on impulse buying through positive emotions.